The Effectiveness of Elderly Gymnastics in Reducing Blood Pressure in Elderly Hypertension Sufferers in RT. 14, Jalan Gedang Subdistrict, Bengkulu City - Dana Wisandi; Puspa Chandra Leka; Delka Mayang Sari; Ria Pitriani; Epet Triana; Fikitri Marya Sari (Universitas Dehasen Bengkulu, 2026)
Hypertension is a common chronic disease among the elderly and poses a risk of serious complications, including stroke, heart disease, and organ dysfunction. This study aimed to evaluate the effectiveness of elderly exercise in reducing blood pressure among hypertensive elderly in RT 14, Jalan Gedang Subdistrict, Bengkulu City. The method used was a community service program involving health education, counseling, and hypertensive exercise practice conducted by 11 students of the S1 KKN students from the Faculty of Health Sciences, Dehasen University, Bengkulu together with cadres and community leaders, in collaboration with community cadres and local leaders. The exercise sessions lasted 30 minutes, recommended to be performed once a week, accompanied by blood pressure monitoring to observe the intervention's effects. Observations showed that the elderly in RT 14 had a high prevalence of hypertension, influenced by lifestyle factors, dietary patterns, and family history. Through this program, the community received education about hypertension, non-pharmacological therapy, and exercise practices that could lower blood pressure and improve the quality of life of the elderly. The program was also supported by the distribution of leaflets as additional educational media. In conclusion, regular elderly exercise integrated with health education can enhance knowledge, awareness, and self-management among the elderly in controlling hypertension. This activity is expected to serve as a sustainable health promotion model for the elderly community in the local area.